2022
DOI: 10.1111/1759-7714.14419
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative plasma fibrinogen levels in resected stage I non‐small cell lung cancer

Abstract: Background: The number of surgical procedures has increased among patients with early-stage lung cancer. If the poor prognostic factors for stage I non-small cell lung cancer (NSCLC) can be simply validated preoperatively, appropriate treatment will be provided. The current study aimed to evaluate the prognostic value of preoperative plasma fibrinogen levels in patients with resected stage I NSCLC. Methods: We retrospectively analyzed the clinicopathological information of patients (n = 149) who underwent lobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Previous studies have shown that coagulation-related factors such as fibrinogen, D-dimer, and platelets are closely related to the prognosis of patients with malignant tumors [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The relationship between fibrinogen and malignant tumors has been widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that coagulation-related factors such as fibrinogen, D-dimer, and platelets are closely related to the prognosis of patients with malignant tumors [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The relationship between fibrinogen and malignant tumors has been widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of fibrinogen increase in inflammatory states as part of the acute-phase response. In patients who underwent surgical resection of stage I NSCLC, those with pre-operative fibrinogen ≥ 377 mg/dl had poorer relapse-free survival (RFS) and OS [38]. D-dimer, prothrombin (PT), activated partial thromboplastin time (APPT), thrombin time (TT), and the international normalised ratio (INR) have also been identified as independent prognostic factors in lung cancer [39,40].…”
Section: Platelets and Coagulation Factorsmentioning
confidence: 99%
“…2023; 22(2): 56-64 фоцитов (neutrophil-to-lymphocyte ratio -NLR)простой и доступный показатель, отражающий дисбаланс между различными звеньями иммунитета [12]; уровень С-реактивного белка и альбумина (Glasgow Prognostic Score) [13]; сочетание NLR, уровня лактатдегидрогеназы (ЛДГ) и уровня экспрессии PD-L1-lung immuno-oncology prognostic score (LIPS-3) [14]; оценка NLR, ЛДГ и уровня альбумина в плазме крови (Gustave Roussy Immune (GRIm)-Score) [15] и, собственно, Lung Immune Prognostic Index (LIPI) -определение NLR и уровня ЛДГ до начала иммунотерапии [16][17][18][19][20][21][22]. Кроме того, возможно включение в прогностическую модель и других клинических доступных факторов, коррелирующих с неблагоприятным прогнозом и достаточно часто выявляемых у пациентов с метастатическим НМРЛ: анемия [23,24], тромбоцитоз [25] и высокий уровень фибриногена [26]. Подобные шкалы с успехом применяются в других нозологиях, например при раке почки.…”
Section: Introductionunclassified